2020
DOI: 10.1029/2019jb018883
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluid Viscosity on Fault Reactivation and Coseismic Weakening

Abstract: High-viscosity fluids are often used during hydraulic fracking operations in georeservoirs. Here we performed dedicated experiments to study the influence of fluid viscosity on fault reactivation and associated induced earthquakes. Experiments were conducted in the rotary-shear machine Slow to HIgh Velocity Apparatus on experimental fault of Westerly granite saturated by fluids with increasing viscosity (at room temperature) from 0.1 mPa s (water) to 1.2 Pa s (99% glycerol). Fault reactivation was triggered at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 68 publications
(113 reference statements)
2
12
0
Order By: Relevance
“…In a different context (no melting), Cornelio et al. (2019, 2020) have shown how viscous fluids permeating natural rock samples affect frictional weakening at high slip velocity by activating elastohydrodynamic lubrication.…”
Section: Nature Of the Frictional Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…In a different context (no melting), Cornelio et al. (2019, 2020) have shown how viscous fluids permeating natural rock samples affect frictional weakening at high slip velocity by activating elastohydrodynamic lubrication.…”
Section: Nature Of the Frictional Interfacementioning
confidence: 99%
“…Though the heating is not localized at the asperity contacts, it is still localized and concentrated within a thin shear layer provided that slip is brief enough (earthquake-like duration, typically seconds) that heat diffusion away from the PSZ is reduced (close to adiabatic conditions). In a different context (no melting), Cornelio et al (2019Cornelio et al ( , 2020 have shown how viscous fluids permeating natural rock samples affect frictional weakening at high slip velocity by activating elastohydrodynamic lubrication.…”
Section: Real and Nominal Contact Areamentioning
confidence: 99%
“…density and viscosity) can influence the rock-fluid interactions (Acosta et al 2018) and, in general, the fault strength. In particular, Cornelio et al (2019Cornelio et al ( , 2020 have recently shown that high fluid viscosity might also play a role in decreasing the dynamic fault strength and, consequently, promoting the propagation of earthquakes. They experimentally showed that the onset of reactivation is independent of the on-fault fluid viscosity (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The source of these signals was found to be the m b 5.4 earthquake in the Fiji Islands region (2013-12-01, 10:01:31.81, -17.574 ○ N -178.261 ○ E, at 535 km depth; International Seismological Centre (2020)), which is at a distance of 144.102 ○ from SDM-1. The travel time of the PKP phase is 1113.34 s (18 min + 33.34 s), as calculated with the travel time toolkit TauP (Crotwell et al, 1999). Thus, the expected arrival time is 10:20:05.15 which fits the onset time of our recorded signal at ∼10:20:05.4 very well (Fig.…”
Section: Earthquakessupporting
confidence: 68%